THE SIGNIFICANCE OF CHESS IN THE DRAMA NATHAN THE WISE OF G.E.LESSING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Chess game is based on a chattering game, which is presented in historical sources. This game was invented in India in the V-VI centuries, and it was called in China, and Japan. In Iran and Arab countries, it has been further improved with the name of shatranj. In Spain in the ninth century it was widely known as chess. In the X-XI centuries this game began to be popular in Europe and Scandinavian countries. The fixed rules of chess were not developed until the XVIII century.